Cytotoxic and Antifungal Terpenoids from Bornean Soft Coral, Sinularia flexibilis - Takashi Kamada; Chin-Soon Phan; Toshiyuki Hamada; Kishio Hatai; Charles Santhanaraju Vairappan (2018)
One new cembrane, ent -sinuflexibilin D (1), along with seven known compounds (2-8) were isolated from a population of Bornean soft coral Sinularia flexibilis. Their structures were elucidated on the basis of spectroscopic analyses. Cytotoxicity and antifungal activities of these compounds were evaluated in vitro. In addition, muurolene 7 was first isolates from a marine source.